English skill of traditional transportation drivers in malioboro yogyakarta - Na'imah, Na'imah (JEES (Journal of English Educators Society), 2022)
English skills are very important for traditional transportation drivers in Malioboro Yogyakarta. This research analyzes the latest facts about the English skills of traditional transportation drivers in Malioboro Yogyakarta, barriers to mastering English, and their impact. The subject of this research is the traditional driver transportation (pedicab and andong) in the tourist area of Malioboro. The data collection techniques are interviews, observation, and documentation. The data analysis technique used in this research is data reduction, data presentation, and conclusion drawing. The results of this study indicate that : (1) the English ability of traditional transportation drivers in Malioboro is still low (2) The inhibiting factors in mastering English are low economy, old age, limited time, low literacy, low education, no training Free English from the government (3) The impact of the inability to communicate in English well is difficulty in making agreement on service rates and less than optimal service delivery. HIGHLIGHTS: The English ability of traditional transportation drivers in Malioboro is still low The inhibiting factors in mastering English are low economy, old age, limited time, low literacy, low education, no training Free English from the government The impact of the inability to communicate in English well is difficulty in agreeing on service rates and less than optimal service delivery.